Knowledge in integrating spiritual aspects in dietetics practice among dietitians in Malaysia - Liyn, Tharine Jyo; Theseira, Kaitlyn Ann; Abdul Jamil, Jamilah; Afandi, Aflah; Arasu, Kanimolli (Universiti Kebangsaan Malaysia (UKM), 2025)
In Malaysia’s multicultural healthcare setting, integrating clients’ spiritual beliefs into dietetic consultations is crucial for holistic care, yet the extent and approaches of such practices remain understudied. This study evaluated Malaysian dietitians’ knowledge of spiritual dietary practices and identified strengths and gaps in the application of this approach in current dietetic practices. A cross-sectional, online survey was conducted among 165 practising Malaysian dietitians. Ten multiple-choice items assessed knowledge of religion-related food practices with scores categorised at a median cut-off of six. Median and interquartile ranges described domain specific knowledge, while response percentages detailed item-level performance. Overall, 69.7% of dietitians scored below the knowledge threshold, indicating limited knowledge on spiritual dietary practices. The study showed the highest proficiency in Islam-related practices (Median = 3, IQR = 2–4), followed by Buddhist, Christian, a nd o ther t raditions (Median = 2, IQR = 2–3), a nd m inimal grasp of Hindu customs (Median = 1, IQR = 1–1). No significant associations were found between knowledge and socio-demographic factors like age, gender, or work setting, suggesting widespread gaps. Strengths included recognition of general religious food restrictions (85.5%), Ramadan post-Tarawih meals (75.2%), and prophetic foods (77.6%). Moderate understanding was seen in identifying non-halal items (59.4%) and Ahimsa in Buddhism (67.3%). Major knowledge gaps were seen in areas like Bahá’í fasting practices (19.4%), vegetarian-linked religions (2.4%), Holy Communion (46.7%), and Sikh avoidance rules (48.5%). While dietitians showed strong understanding of Islamic dietary practices, their cross-faith spiritual knowledge, especially of minority traditions, remained limited. Targeted, faith specific educational interventions are needed to enhance spiritual competence and support more culturally sensitive dietetic care.